Pb isotopes in the impact melt breccia 66095: Association with the Imbrium basin and the isotopic composition of lithologies at the Apollo 16 landing site - Snape, J.; Nemchin, Alexander; Bellucci, J.; Whitehouse, M. (Elsevier Science BV, 2017)
© 2017 Elsevier B.V. Recent in situ Secondary Ion Mass Spectrometry (SIMS) Pb isotope analyses of lunar basalts have provided precise crystallisation ages and initial Pb isotopic compositions for these samples. In this study, the same approach has been tested in the Apollo 16 impact melt breccia 66095, referred to as the “Rusty Rock” due to its enrichments in volatile elements, including Pb. Based on these analyses of the breccia, a Pb-Pb isochron age of 3909 ± 17 Ma (at the 95% confidence level) and an initial Pb composition for 66095 have been determined. This age is interpreted as representing the time of breccia formation that, when combined with recent studies of lunar breccias, can be linked to the Imbrium basin forming impact. The directly measured initial Pb composition of the breccia from this work is similar a modelled compositions presented previously, and likely reflects an average value for the lithologies present at the Apollo 16 landing site at the time that the Imbrium ejecta was emplaced. The 66095 initial Pb isotopic composition is compared with the compositions in other lunar samples and the nature of the endmember lithologies in this mixture has been discussed within the framework of a multiple stage model of Pb isotope evolution on the Moon. This study demonstrates the effectiveness of this technique beyond its application in crystalline basalts, opening up the possibility of obtaining precise geochronological and Pb isotopic compositions from a broader sample set than was previously recognised.